Effect of intravenous N-acetylcysteine infusion on haemostatic parameters in healthy subjects. Issue 4 (7th March 2005) - Knudsen, T T; Thorsen, S; Jensen, S A; Dalhoff, K; Schmidt, L E; Becker, U; Bendtsen, F
Abstract : Background and aim: N-acetylcysteine is used to treat paracetamol overdose but depresses the activity of plasma coagulation factors II, VII, and X, which are often used to assess liver injury. The aim of this study was to investigate the effect of N-acetylcysteine on haemostasis in normal volunteers. Methods: Haemostatic parameters in 10 healthy subjects were analysed before and following intravenous infusion of therapeutic doses of N-acetylcysteine, as well as in vitro. Results: N-acetylcysteine induced significant decreases in plasma levels of vitamin K dependent haemostatic proteins in vivo, being maximal at one hour following the start of infusion, with maximal decreases from 1.00 to 0.73 (0.67–0.79) (mean (95% confidence interval)), 0.66 (0.58–0.73), 0.81 (0.73–0.90), 0.64 (0.57–0.70), 0.74 (0.65–0.82), and 0.61 (0.54–0.67) for factor II, VII, IX, and X activities, protein C activity, and free protein S reactivity, respectively. These data suggest that N-acetylcysteine induces protein modifications affecting activity. Five subjects developed an adverse reaction to infusion of N-acetylcysteine and these were associated with a rapid increase in levels of factor VIII and its carrier protein von Willebrand factor (vWf) from 1.0 to 1.85 (1.08–2.62) and 1.77 (0.83–2.71), respectively, which suggests that the allergic reaction induced release of vWf from endothelial cells. N-acetylcysteine did not affect factor VIII or vWf in subjects without adverse reactions, and nor did it affect factor V or antithrombin in any of the subjects. Conclusion: Therapeutic doses of N-acetylcysteine cause abnormal haemostatic activity, and this should be taken into account when using haemostatic function tests as an indicator of hepatic injury.